Directive Speech Acts in English Teachers’ Classroom Talk: A Discourse Analysis in Indonesian Vocational High School - Nuraeni; Didin Nuruddin Hidayat; Nida Husna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the use of directive speech acts in an English teacher’s classroom talk at an Indonesian vocational high school. It explores how these directives support classroom management and interaction in EFL learning. One teacher and 34 eleventh-grade OTKP students participated in the study. The classroom observation spanned three class meetings, totaling four instructional hours, and was conducted over a two-week data collection period. Data were collected through classroom observations, video recordings, transcripts of teacher-student interaction, and field notes. The teacher was purposively selected for active engagement in classroom communication and willingness to be observed, making the participant appropriate for the research aims. Employing a qualitative discourse analysis design, the study identified the types and functions of directives used during instruction based on Searle’s (1979) and Yule’s (1996) classifications. A total of 25 directive speech acts were found: seven commands, nine requests, three suggestions, four invitations, and two prohibitions. Commands and requests appeared most frequently, showing how the teacher balanced classroom control with student involvement. Suggestions and invitations supported comprehension and participation, while prohibitions helped maintain order. The findings indicate that directive speech acts play central managerial and pedagogical roles in shaping classroom interaction. In addition to contributing to pragmatic and classroom discourse research, the study offers practical implications for teaching, emphasizing the need for teachers to intentionally employ directives to guide learning, sustain engagement, and create a more supportive, well-managed EFL classroom.